Multifactorial e- and mHealth interventions for cardiovascular disease primary prevention: Protocol for a systematic review and meta-analysis of randomised controlled trials. (November 2019) - Direito, Artur; Rawstorn, Jonathan; Mair, Jacqueline; Daryabeygi-Khotbehsara, Reza; Maddison, Ralph; Tai, E Shyong
Objective: Cardiovascular diseases (CVD) are a leading cause of mortality and disease burden. Preventative interventions to augment the population-level adoption of health lifestyle behaviours that reduce CVD risk are a priority. Face-to-face interventions afford individualisation and are effective for improving health-related behaviours and outcomes, but they are costly and resource intensive. Electronic and mobile health (e- and mHealth) approaches aimed at modifying lifestyle risk factors may be an effective and scalable approach to reach many individuals while preserving individualisation. This systematic review aims to (a) determine the effectiveness of multifactorial e- and mHealth interventions on CVD risk and on lifestyle-related cardiometabolic risk factors and self-management behaviours among adults without CVD; and (b) describe the evidence on adverse events and on the cost-effectiveness of these interventions. Methods: Methods were detailed prior to the start of the review in order to improve conduct and prevent inconsistent decision making throughout the review. This protocol was prepared following the PRISMA-P 2015 statement. MEDLINE, CINAHL, Embase, PsycINFO, Web of Science, Cochrane Public Health Group Specialised Register and CENTRAL electronic databases will be searched between 1991 and September 2019. Eligibility criteria are: (a) population: community-dwelling adults; (b) intervention/comparison: randomised controlled trials comparing e- or mHealth CVD risk preventative interventions with usual care; and (c) outcomes: modifiable CVD risk factors. Selection of study reports will involve two authors independently screening titles and abstracts, followed by a full-text review of potentially eligible reports. Two authors will independently undertake data extraction and assess risk of bias. Where appropriate, meta-analysis of outcome data will be performed. Discussion: This protocol describes the pre-specified methods for a systematic review that will provide quantitative and narrative syntheses of current multifactorial e- and mHealth CVD preventative interventions. A systematic review and meta-analysis will be conducted following the methods outlined in the Cochrane Handbook for Systematic Reviews of Interventions and reported according to PRISMA guidelines.